2017
DOI: 10.1002/chem.201701596
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Construction of Self‐Assembled Heterometallic Cages Showing High Proton Conductivity

Abstract: Two neutral tripodal metalloligands (CoL and FeL where L=C H N ) containing a clathrochelate core were synthesized and characterized in one-step. Reactions of these ligands with three different metal acceptors cis-(tmen)Pd(NO ) (tmen = tetramethylethylenediamine), Zn(NO ) and Mn(ClO ) separately yielded a series of heterometallic coordination cages (1 a-3 a and 1 b-3 b) in high yields. Depending on the nature of coordination geometry of the acceptors, the resulting assemblies have trigonal- bipyramidal (1 a/1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 136 publications
(14 reference statements)
0
24
2
2
Order By: Relevance
“…The influenceo faweakly-coordinating anion on the structure of the product was investigated using Co(BF 4 ) 2 ·6 H 2 Oi n place of CoCl 2 (Figure 9a). Slow diffusion of alayered MeCN solution of Co(BF 4 ) 2 ·6 H 2 Oi nto aC H 2 Cl 2 solution of 1 at À30 8C for one week produced pink needles, identified by X-ray crystallography as [Co 5 (1) 6 (H 2 O) 6 (NCMe) 6 ][BF 4 ] 10 (in 58 %y ield) (see Experimental Section) ( Figure 9b). The X-ray data show ar apid drop-off in intensity as af unctiono fs cattering angle, leading to challenges with the refinement (see ESI), but the connectivity and structural arrangemento ft he complex are provedu nambiguously.T he structure was confirmedf or several crystals obtained from different reaction batches.T he structure contains ac ationic [Co 5 (1) 6 (H 2 O) 6 (NCMe) 6 (&BF 4 ) 2 ] 8 + (Co 5 Sn 6 )c age in which two BF 4 À anionsa re encapsulated (with the remaining eight residingi nt he crystal lattice).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influenceo faweakly-coordinating anion on the structure of the product was investigated using Co(BF 4 ) 2 ·6 H 2 Oi n place of CoCl 2 (Figure 9a). Slow diffusion of alayered MeCN solution of Co(BF 4 ) 2 ·6 H 2 Oi nto aC H 2 Cl 2 solution of 1 at À30 8C for one week produced pink needles, identified by X-ray crystallography as [Co 5 (1) 6 (H 2 O) 6 (NCMe) 6 ][BF 4 ] 10 (in 58 %y ield) (see Experimental Section) ( Figure 9b). The X-ray data show ar apid drop-off in intensity as af unctiono fs cattering angle, leading to challenges with the refinement (see ESI), but the connectivity and structural arrangemento ft he complex are provedu nambiguously.T he structure was confirmedf or several crystals obtained from different reaction batches.T he structure contains ac ationic [Co 5 (1) 6 (H 2 O) 6 (NCMe) 6 (&BF 4 ) 2 ] 8 + (Co 5 Sn 6 )c age in which two BF 4 À anionsa re encapsulated (with the remaining eight residingi nt he crystal lattice).…”
Section: Resultsmentioning
confidence: 99%
“…[2] Severin and co-workersh ave overcome this tendency by incorporatinga dditional steric groups into bis(3-pyridyl) Fe clathrochelate ligandst op roduce Pd 6 L 12 12 + cages, [2] and have found that tuningt he sterics alters the size of the cage. [3] This metalloligand strategy for the construction of heterometallic supramolecular architectures has been successfully enacted for av ariety of mixed transition metals ystems, for example, Fe/Pd, [2,[4][5][6] Fe/Ru, [7] Fe/Co, [8,9] Co/ Mn [5] and Ru/Pd. [10,11] However,t he use of main group metalloligands to createmixed main group/transitionmetal heterometallic systems is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible to transfer all advantages of the subcomponent self‐assembly approach to systems consisting of more than one type of metal cation. However, to date only a few examples of heterobimetallic complexes have been reported that were built up from subcomponents …”
Section: Methodsmentioning
confidence: 99%
“…Increasing the structural complexity, however, usually implies growing synthetic efforts that have to be made to obtain the necessary organic ligands [15][16][17]. A great way to simplify ligand syntheses is the subcomponent self-assembly strategy [18][19][20][21][22][23]. Following this strategy, the actual ligand is generated in situ during the self-assembly process via reversible formation of covalent bonds, in most cases imine bonds.…”
Section: Introductionmentioning
confidence: 99%
“…elements of both metal centers, and hence, access new geometries. Reliable design strategies like the complex-as-a-ligand approach made the assembly of heterobimetallic structures predictable; hence, there is a rapidly growing number of heterobimetallic structures that has recently been described in the literature, such as, e.g., helicates [27,28], cubes [29][30][31], trigonal bipyramids [21,32,33], boxes [34][35][36], prismatic cages [37], or some truly unique other shapes [38,39]. At the same time, heterobimetallic cages not only offer the chance to obtain new geometries, the combination of two different metal cations within one aggregate might also lead to enhanced or even entirely new properties and functions [40].…”
Section: Introductionmentioning
confidence: 99%